2006
DOI: 10.1520/jai12425
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Creep of Irradiated Zircaloy Cladding

Abstract: As part of an effort to investigate spent-fuel behavior during dry-cask storage, thermal creep tests are being performed with defueled Zircaloy-4 cladding segments from two pressurized water reactors — Surry at ≈36 GWd/MTU burnup and H. B. Robinson at ≈67 GWd/MTU burnup, with corresponding fast (E > 1 MeV) fluence levels of 7×1025 and 14×1025 n/m2. The Surry rods are particularly relevant because they were stored in an inert-atmosphere (He) cask for 15 years. The Robinson rods were received after reacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 4 publications
0
20
0
1
Order By: Relevance
“…A comparison of these results with the equivalent data from the Zr-4 H.B. Robinson rod [6], with similar burnup and hydrogen content as the ZIRLO rod, may suggest similar creep behaviour of Zr-4 and ZIRLO.…”
Section: Test Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…A comparison of these results with the equivalent data from the Zr-4 H.B. Robinson rod [6], with similar burnup and hydrogen content as the ZIRLO rod, may suggest similar creep behaviour of Zr-4 and ZIRLO.…”
Section: Test Resultsmentioning
confidence: 65%
“…Although according to existing research [6], significant annealing should be observed after 72 hours at 420ºC, this effect is not discernible after 330 hours at 400ºC or an even longer period, 1000 hours, at 380ºC. Therefore, it may be concluded that the performed microhardness evaluation would support the idea that the acceleration on the measured creep is not due to the thermal annealing of the irradiation damage.…”
Section: Post Test Characterizationmentioning
confidence: 82%
See 2 more Smart Citations
“…사용후핵연료의 건전성에 영향을 미칠 수 있는 요인 들로는 크립(creep) [5][6][7]과 수소화물재배열 [8][9][10], 지연수 소화균열(Delayed Hydride Cracking, DHC) [11][12][13], 응력 부식균열 [14,15], 산화 및 부식에 의한 파괴 등을 들 수 있 다 [16]. 미국 원자력안전규제위원회(U.S. Nuclear Regula- …”
Section: 서 론unclassified